Analisis Komparasi Hapiness Index 5 Negara di Asean - I Wayan Suparta; Rizka Malia (Jurnal Ekonomi Pembangunan, 2020)
The limitation of economic indicators in representing the level of community welfare has increased the world's attention to social aspects of development. Development progress, which has been seen more by economic indicators, such as economic growth and poverty reduction, is considered insufficient to reflect the right level of welfare. This study aims to determine the effect of GDP per capita, environmental index, and unemployment on the happiness index of 9 countries in ASEAN. Estimation results show that the variable GDP per capita significantly and negatively influences the happiness index. The environmental index has a positive effect on the Happiness Index, and unemployment has a positive impact on the happiness index. Based on the results of special effects, there are individual effect values ​​in 9 ASEAN countries. Singapore is the country with the most significant personal impact, and the Philippines is the country with the smallest particular effect.